Longitudinal evaluation of structural brain alterations in two established mouse models of Gulf War Illness - Carpenter, Jessica M.; Hughes, Sarah N.; Filipov, Nikolay M. (Frontiers in Neuroscience, 2024)
Gulf War Illness (GWI) affects nearly 30% of veterans from the 1990–1991 Gulf War (GW) and is a multi-symptom illness with many neurological effects attributed to in-theater wartime chemical overexposures. Brain-focused studies have revealed persistent structural and functional alterations in veterans with GWI, including reduced volumes, connectivity, and signaling that correlate with poor cognitive and motor performance. GWI symptomology components have been recapitulated in rodent models as behavioral, neurochemical, and neuroinflammatory aberrations. However, preclinical structural imaging studies remain limited. This study aimed to characterize the progression of brain structural alterations over the course of 12 months in two established preclinical models of GWI. In the PB/PM model, male C57BL/6 J mice (8–9 weeks) received daily exposure to the nerve agent prophylactic pyridostigmine bromide (PB) and the pyrethroid insecticide permethrin (PM) for 10 days. In the PB/DEET/CORT/DFP model, mice received daily exposure to PB and the insect repellent DEET (days 1–14) and corticosterone (CORT; days 7–14). On day 15, mice received a single injection of the sarin surrogate diisopropylfluorophosphate (DFP). Using a Varian 7 T Bore MRI System, structural (sagittal T2-weighted) scans were performed at 6-, 9-, and 12-months post GWI exposures. Regions of interest, including total brain, ventricles, cortex, hippocampus, cerebellum, and brainstem were delineated in the open source Aedes Toolbox in MATLAB, followed by brain volumetric and cortical thickness analyses in ImageJ. Limited behavioral testing 1 month after the last MRI was also performed. The results of this study compare similarities and distinctions between these exposure paradigms and aid in the understanding of GWI pathogenesis. Major similarities among the models include relative ventricular enlargement and reductions in hippocampal volumes with age. Key differences in the PB/DEET/CORT/DFP model included reduced brainstem volumes and an early and persistent loss of total brain volume, while the PB/PM model produced reductions in cortical thickness with age. Behaviorally, at 13 months, motor function was largely preserved in both models. However, the GWI mice in the PB/DEET/CORT/DFP model exhibited an elevation in anxiety-like behavior.